PENERBITAN SURAT PERSETUJUAN BERLAYAR KAPAL PERIKANAN PADA KANTOR UNIT PENYELENGGARA PELABUHAN BANGGAI - Noval Djewed (Jurnal Yustisiabel, 2020)
In the context of shipping protection and safety, it is necessary to obtain approval of the Sailing Agreement by Syahbandar. This paper is to find out the procedures approved by the Fishing Boat Approval Letter at the Banggai Port Operator Unit Office, and to find out and analyze the factors that influence it. The research used is empirical juridical with primary, secondary and tertiary data collection. Procedures for approving Fishing Vessel Approval Letters at the Banggai Port Operational Unit Office, approving applications for approval of Sailing (SPB), checking the administration and physical condition of vessels, and issuing Sailing Approval Letters (SPB). As a factor influencing the Fishing Boat Sail Approval Letter in the Banggai Port Operator Unit Office, it consists of supporting factors, namely legal factors and supporting factors. While the inhibiting actors are the Number of Human Resources and the inaccuracy of applicants.